Continuity and change in sporting and leisure time physical activities during adolescence - Dovey, S M; Reeder, A I; Chalmers, D J (British journal of sports medicine, 1998)
OBJECTIVES: To map the pattern of involvement in physical activities by adolescents at ages 15 and 18 years. METHODS: Data from a longitudinal cohort study were used. Participants in the Dunedin Multidisciplinary Health and Development Study provided information about their sporting and similar physical activities during the 12 months before study assessments at ages 15 and 18 years. RESULTS: Total participation time at age 18 was 63% of that reported at age 15. Mean participation time for girls decreased from 7.5 hours a week to 4.3 hours a week (p<0.001) whereas for boys it decreased from 11.7 hours a week to 7.8 hours a week (p<0.001). At both ages, boys spent significantly more time in physical activity than girls. More time in physical activity at age 18 was reported by participants who judged their fitness higher than their peers (odds ratio (OR) 1.7: 1.2, 2.5), those who played sport for their school (OR 1.8: 1.3, 2.4), and those reporting very good self assessed health (OR 1.4: 1.0, 1.8) at age 15. The overall median number of activities decreased from seven at age 15 to three at 18. Boys were involved in more activities at age 15 but there was no sex difference at age 18 in the number of different activities reported. CONCLUSION: Although involvement in school sporting activities and high levels of fitness in mid-adolescence may protect against marked reductions in physical activity in late adolescence, social and organisational factors are also likely to be important. There is a need for innovative approaches to health promotion which will encourage adolescents to maintain higher levels of physical activity after they leave school.